Birds - Mohd Azlan, Jayasilan; Sally, Soo Kaicheen; Lok, Lisa Choy Hong; Voon, Audrey Mei Fang (UNIMAS Publisher and Wilmar Plantations Sdn Bhd, 2023)
Significant proportions of the Bornean rainforest have been converted to agricultural landscapes (i.e. oil palm (Elaeis guineensis Jacq) plantation), resulting in many of its remaining forests being fragmented and isolated. These forest patches are regarded as ecologically depauperate and have lower conservation value as many keystone species are absent, which has reduced ecological functions (Miller-Rushing et al., 2019). However, to minimise the impact of the monoculture plantations on the ecosystem, forest remnants’ roles should not be neglected as they retain some of the biodiversity remnants. Additionally, forest fragments that maintain a certain degree of environmental or social significance are regarded as high conservation value forests (HCVF) (Jennings et al., 2003).